Collaborative Mid-Point Voltage Regulation in Low-Switching-Frequency MPC for Three-Level NPC Inverters Fed Dual Three-Phase PMSM Drives - Minrui Gu; Zheng Wang; Congjian Wen; Zhixiang Zou (IEEE Open Journal of Power Electronics, 2021)
In this paper, the control strategy is studied for the neutral-point-clamped three-level (NPC-3L) dual three-phase permanent-magnet synchronous machine (PMSM) drives at low-switching-frequency operation. The finite-control-set (FCS) model predictive control (MPC) scheme is investigated as the basic MPC scheme, where the average switching frequency is established as the cost function. With the high sampling frequency operation, the discretization with both forward and backward Euler methods is utilized so that the two sets of three-phase windings are controlled separately. To further decrease the switching frequency while maintaining the current and voltage control performance, a collaborative mid-point voltage regulation is proposed. The collaborative regulation strategy fully employs the additional control degree of freedom in the dual three-phase drives by setting the two NPC-3L inverters to select small vectors with opposite polarities. Therefore, the situation is avoided where the upper or the lower capacitor in the DC link provides load currents for the two sets of windings simultaneously. Simulation results of a 2.45 MW dual three-phase drive and experimental results on a laboratory prototype have been presented to verify the validity of the proposed collaborative mid-point voltage regulation strategy.